2019
DOI: 10.3390/f10050458
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Methods and the Use of Location and Activity Data in Forests

Abstract: In this paper, we provide an overview of positioning systems for moving resources in forest and fire management and review the related literature. Emphasis is placed on the accuracy and range of different localization and location-sharing methods, particularly in forested environments and in the absence of conventional cellular or internet connectivity. We then conduct a second review of literature and concepts related to several emerging, broad themes in data science, including the terms location-based servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 218 publications
1
27
0
1
Order By: Relevance
“…If a precise position can be obtained by a technique that does not rely on differential correction, the data processing of the receiver can be simplified, and the cost can be reduced. GNSSs have increasingly been playing roles in positioning forest fires [8], mapping forest resources [9], inventorying forest resources [10], positioning fixed sample sites [11], mapping roads [12], and measuring other natural resources [13].…”
Section: Introductionmentioning
confidence: 99%
“…If a precise position can be obtained by a technique that does not rely on differential correction, the data processing of the receiver can be simplified, and the cost can be reduced. GNSSs have increasingly been playing roles in positioning forest fires [8], mapping forest resources [9], inventorying forest resources [10], positioning fixed sample sites [11], mapping roads [12], and measuring other natural resources [13].…”
Section: Introductionmentioning
confidence: 99%
“…10 Using global navigation satellite system (GNSS) enabled radios and smartphones, the research team demonstrated that the movements of hand fallers on cable logging operations could be quantified using activity recognition models based on smartphone sensors. 11,12 Currently, field studies are underway with rigging crews to assess if fitness watches can provide equivalent movement data compared to smartphone sensors. Long-term goals include the production of tools to quantify hazardous work activities, improve incident detection, and decrease response time.…”
Section: Session -New Technologies Transforming Loggingmentioning
confidence: 99%
“…Remote machine monitoring was explored already many years ago-more than a decade in Northern Europe, for instance-but it is now quite common with modern forest machines used worldwide. In fact, the use of smart phones now allows real-time communication and the automatic collection of production data from manual operations, as well [65].…”
Section: It Technology and The Internet Of Thingsmentioning
confidence: 99%